Hybrid Solar Geothermal Heat Pump System Model Demonstration Study - Kim, Yu-Jin; Yang, Libing; Entchev, Evgueniy; Cho, Soolyeon; Kang, Eun-Chul; Lee, Euy-Joon (Frontiers in Energy Research, 2022)
The Korean government announced energy policies to reduce greenhouse gases emissions 37% by 2030 and had a plan to implement the renewable energy 20% by 2030. They introduced zero energy building obligation for the public building from 2020 and for private building from 2025. To reach these goals in Korea, a variety of renewable technologies need to be introduced. In this paper, a solar geothermal heat pump hybrid poly generation system has been designed and modeled in TRNSYS and demonstrated in a building located Cheongju Korea. The heating and cooling load of the demonstration system are 13.8 kW heating for ambient temperature -10.3℃ and 10.6 kW cooling for ambient temperature 32.3℃ respectively for the design temperatures. Justification of the poly generation system has been conducted by comparing ISO 13256 based lab WWHP COPc data with the demonstration WWHP COPc data. The source temperature of WWHP was 16.7℃ the WWHP lab performance data based COPc shows 9.9 while demonstration COPc shows 10.3 representing 4.3 % relative error. The WWHP source temperature was decrease 4.1℃ from 20.9℃ to 16.8 by a GHX couplng in cooling mode and increasing the COPc 13% from 8.5 to 9.8. When ambient temperature is the design cooling temperature 32.3℃, the TRSNYS model WWHP cooling load indicated 9.3 kW and the demonstration model WWHP cooling load indicated 8.1 kW and the TRNSYS component model overestimated the demonstration site data by 12%. When ambient temperature is the design cooling temperature 32.3℃, the TRSNYS model cooling system power consumption indicated 3.1 kW and the demonstration model system power consumption indicated 2.2 kW. The power consumption of this solar geothermal heat pump hybrid poly generation system decreased to 2.6 kWw from 3.8kW to 1.2 kW while ambient temperature decreased from 35℃ to 25℃.